Police and community in Chicago a tale of three cities - Skogan, Wesley G. (Oxford : Oxford University Press, 2006)
In the early 1990s, Chicago, the nation's third largest city, instituted the nation's largest community policing initiative. Wesley G. Skogan here provides a comprehensive evaluation of that citywide programme, examining its impact on crime, neighbourhood residents, and the police.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Chicago (Ill.). -- Police Dept; Community policing -- Illinois -- Chicago; Crime prevention -- Illinois -- Chicago -- Citizen participation